Dynamic Changes in the Renin-Angiotensin-Aldosterone System and the Beneficial Effects of Renin-Angiotensin-Aldosterone Inhibitors on Spatial Learning and Memory in a Rat Model of Chronic Cerebral Ischemia - Huang, Xinwu; Lu, Guozhou; Li, Guochun; Li, Hua; Li, Beihua; Yin, Jiazhen; Cao, Shousong (Frontiers in Neuroscience, 2017)
Renin-angiotensin-aldosterone system (RAAS) plays an important role in the regulation of blood pressure and brain function. Therefore, we studied the dynamic changes in the RAAS in the blood, cerebral cortex and hippocampus and the effects of RAAS inhibitors on spatial learning and memory and hippocampal apoptosis in a rat model of chronic cerebral ischemia (CCI) established by bilateral ligation of the common carotid arteries of rats. The levels of renin, angiotensin II (Ang II), and aldosterone (ALD) in the plasma, and the homogenates of the left side of cerebral cortex and whole hippocampus of rats were detected on day 1, 3, 7, 14, 21, and 30 by radioimmunoassay. Spatial learning and memory and hippocampal apoptosis were evaluated on day 30 by Morris water maze test (navigation and space exploration tests) and terminal dexynucleotidyl transferase (TdT)-mediated dUTP nick end labeling (TUNEL) assay, respectively, after rats were orally administered with distilled water (DW), renin inhibitor aliskiren (30 mg/kg/), Ang converting enzyme inhibitor enalapril (4 mg/kg), or Ang II receptor antagonist candesartan (2 mg/kg) daily for 30 days. The results showed that the levels of renin and Ang II were significantly higher but ALD fluctuated in the blood, cerebral cortex and hippocampus in CCI rats compared to normal rats. However, aliskiren and enalapril could significantly decrease (p < 0.05) the levels of renin, Ang II and ALD in the blood, cerebral cortex and hippocampus compared to DW treatment; while candesartan had similar effect on renin and ALD but no effect on Ang II in CCI rats. Furthermore, spatial learning and memory were significantly decreased but apoptosis in the hippocampus was obviously increased in CCI rats compared to normal rats (p < 0.05). However, aliskiren, enalapril, and candesartan were equally effective to improve spatial learning and memory and decrease apoptosis in the hippocampus. Therefore, RAAS plays an important role in the development of cerebral ischemia and RAAS inhibitors aliskiren, enalapril, and candesartan improve spatial learning and memory and protect brain injury by inhibiting hippocampal apoptosis in CCI rats.